2019
DOI: 10.1186/s12911-019-0811-2
|View full text |Cite
|
Sign up to set email alerts
|

Are Austrian practitioners ready to use medical apps? Results of a validation study

Abstract: Background As part of the mobile revolution, smartphone-based applications (apps) have become almost indispensable in today’s information society. Consequently, the use of medical apps among healthcare professionals has increased heavily over the past years. As little is known on medical app use in day-to-day clinical practice in Austria, the present study aims at closing this knowledge gap by assessing respective prevalence, readiness, and concerns among Austrian practitioners. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 40 publications
(56 reference statements)
8
53
0
2
Order By: Relevance
“…Though the rate was lower compared with the installment of Wechat and QQ, the number was still in agreement with many other studies in other areas of the world [13,16,19]. Our study found that there were signi cant differences between gender, age and whether or not installing medical apps.…”
Section: Discussionsupporting
confidence: 91%
“…Though the rate was lower compared with the installment of Wechat and QQ, the number was still in agreement with many other studies in other areas of the world [13,16,19]. Our study found that there were signi cant differences between gender, age and whether or not installing medical apps.…”
Section: Discussionsupporting
confidence: 91%
“…Only 76% participants (n = 288) installed medical app (except Wechat and QQ) on their smartphones. Though the rate was lower compared with the installment of Wechat and QQ, the number was still in agreement with many other studies in other areas of the world [14,15,20]. Our study found that there were signi cant differences between gender, age and whether or not installing medical apps.…”
Section: Discussionsupporting
confidence: 91%
“…Only 76% of the participants (n = 288) installed a medical app (other than WeChat and QQ) on their smartphones. Though the rate was lower compared with the installation of WeChat and QQ, the number was still in agreement with many studies in other areas of the world [14,15,20]. Our study found that there were signi cant differences in whether medical apps were installed by gender and age.…”
Section: Discussionsupporting
confidence: 90%